Massive B-Cell Infiltration and Organization Into Artery Tertiary Lymphoid Organs in the Aorta of Large Vessel Giant Cell Arteritis - Graver, Jacoba C.; Boots, Annemieke M. H.; Haacke, Erlin A.; Diepstra, Arjan; Brouwer, Elisabeth; Sandovici, Maria (Frontiers in Immunology, 2019)
Giant cell arteritis (GCA) can be classified into Cranial(C)-GCA and Large Vessel(LV)-GCA. Based on analysis of temporal arteries, GCA is postulated to be T-cell-mediated. Recently, a disturbed B-cell homeostasis was documented in newly diagnosed GCA patients. In the current study, we assessed the presence of B-cells and their level of ectopic organization in the aorta of LV-GCA patients. Aorta tissue samples of 9 histologically-proven LV-GCA patients and 22 age- and sex-matched atherosclerosis patients who underwent aortic aneurysm surgery were studied by immunohistochemistry. Sections were stained for B-cells, T-cells, follicular dendritic cells, high endothelial venules, germinal center B-cells, proliferating B-cells, macrophages and plasma cells. Aortas of LV-GCA patients showed massive infiltration of B-cells, which clearly outnumbered T-cells, as opposed to C-GCA patients where, as previously reported, T-cells outnumber B-cells. B-cells were mainly found in the adventitia of the vessel wall and were organized into artery tertiary lymphoid organs. These tertiary lymphoid organs had germinal centers, proliferating B-cells and plasma cell niches. In conclusion, we found massive and organized B-cell infiltrates in the aorta of LV-GCA patients, which is in line with the previously documented decrease of circulating B-cells in active GCA. Our data indicate a role for B-cells in the pathogenesis of GCA and thus evoke further investigation into the factors determining the tissue tropism and organization of B-cells in GCA.